Boosting the photoelectrochemical activities of all-inorganic perovskite SrTiO3 nanofibers by engineering homo/hetero junctions. Issue 36 (31st August 2018) - Liang, Zhao; Hou, Huilin; Song, Kai; Zhang, Kan; Fang, Zhi; Gao, Fengmei; Wang, Lin; Chen, Ding; Yang, Weiyou; Zeng, Haibo
Abstract : We report a strategy of engineering homo/hetero junctions for boosting the PEC activities of all-inorganic perovskite SrTiO3 nanofibers with high photocurrent density and stability. Abstract : In the current work, we reported the engineering of homo/hetero junctions for boosting the photoelectrochemical (PEC) behaviors of all-inorganic perovskite SrTiO3 (STO) nanofibers. The engineering of these junctions was accomplished via spin-coating and electrospinning, followed by atomic layer deposition (ALD). The introduced STO film leads to the formation of the STO/STO homojunction, which provided an extended contact area to enhance the electron–hole mobility across the interface. Meanwhile, ALD-deposited ZnO allowed for the construction of the STO/ZnO heterojunction, which could build up internal electric fields at the interface to hinder the recombination of electron–hole pairs, causing a totally enhanced photoelectrochemical (PEC) activity. As a proof of concept, at an applied bias of 1.23 V vs. RHE, the photocurrent density of STO nanofibers with engineered homo/hetero junctions was enhanced more than 600 times that of their pristine STO counterpart. At 0 V vs. Ag/AgCl, their photocurrent density was improved up to ∼61.3 μA cm −2 in comparison to 0.12 μA cm −2 of their pristine STO counterpart. Furthermore, their photocurrent stability was increased from 79.62% of their pristine STO counterpart to 98% at 0.1 V vs. Ag/AgCl.